Synthesis and characterization of Ga-substituted MER-type zeolites - Kim, SH; Kim, SD; Kim, YC; Kim, CS; Hong, SB (ELSEVIER, 2001)
Ga-substituted merlinoite (MER)-type zeolites are hydrothermally synthesized using aluminosilicate MER crystals as seeds under wholly inorganic conditions. The presence of Ga in tetrahedral positions is evidenced by powder X-ray diffraction, Si-29 and Ga-71 MAS NMR, and IR spectroscopies. The bulk Si/(Ga + Al) ratio in the framework determined by elemental analysis is in the range 1.9-3.0, depending on the initial Si/Ga ratio of the synthesis mixture. An attempt to fully substitute framework Al by Ga was not successful: a gallosilicate with GIS topology, denoted TNU-2, is produced when aluminosilicate MER seed crystals are not added to the synthesis mixture. This clearly shows that the structure-directing ability of Ga is different from that of Al in the synthesis conditions used here. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: GALLIUM